USING AQUATIC PLANTS AS TREATMENT FOR SWINE-BREEDING WASTEWATER AFTER BIOGAS TECHNOLOGY - Thi Thuy An, Thai; Thi Ngoc Bich, Nguyen; Huy Cuong, Nguyen (Journal of Forestry Science and Technology, 2023)
The livestock industry is one of the important sectors of agriculture in Vietnam. The swine-breeding farms are mainly spontaneous, the common wastewater is treated by biogas technology. However, the actual operation at the farms, shows that the wastewater treatment by biogas has been high content and still exceeded the standards of national regulation QCVN 62-MT:2016/BTNMT of COD, BOD5, TN, PO43-, leading to affect the environment. An empirical study was carried out to treat swine-breeding wastewater after biogas technology using Sagittaria sagittifolia and Enydra fluctuans. The results showed that the swine-breeding farming wastewater treatment model with Enydra fluctuans has an efficiency of 73.3% of COD content, 89.2% of BOD5, 88.3% of TN, and 89.6% of PO43-. Sagittaria sagittifolia showed a yield of 66.7% of COD content, 78.7% of BOD5, 69.5% of TN, and 85.1% of PO43-. With the same conditions and the same experimental design method, Enydra fluctuans showed better treatment results than Sagittaria sagittifolia. However, wastewater is treated by Sagittaria sagittifolia and Enydra fluctuans meeting the regulations QCVN 62-MT:2016/BTNMT, column B for pH, COD, BOD5, TN, PO43- parameters after 30 days. The treatmen model shows great potential for using aquatic plants to remove pollutants from swine-breeding wastewater. However, further studies should be carried out to evaluate the model’s stability and applicability in practice.